Respostas

  • Usuário do Brainly
2013-10-22T23:11:58-02:00
2x + 1 = 5
2x = 5 - 1
2x = 4
x = 4/2
x = 2
------------
2y + 4 = 12
2y = 12 - 4
2y = 8
y = 8/2
y = 4
------------
5y + 6 = 2
5y = 2 - 6
5y = - 4
y = -4/5
-----------
3y + 3 = - 9
3y = - 9 - 3
3y = - 12
y = - 12/3
y = - 4
-------------
2x - 1 = 9
2x = 9 + 1
2x = 10
x = 10/2
x = 5
------------
3x - 4 = 19
3x = 19 + 4
3x = 23
x = 23/3
------------
4y - 5 = 13
4y = 13 + 5
4y = 18
y = 18/4 (simplifique por 2)
y = 9/2
-----------------
5y + 12 = - 18
5y = - 18 - 12
5y = - 30
y = - 30/5
y = - 6